(untitled) (Research, Society and Development, 2020)
Attention to care for the pregnant woman and the newborn represents a priority field within the health care of the populations and, in order for it to develop in a more effective / efficient way, a solid performance of the services and the health care system is necessary. Cheers. This study aimed to explain about the importance of the role of the obstetric nurse in primary care. For the construction of the article, a integrative literature review was carried out on articles in the Scielo, PubMed and Lilacs databases, published in the last ten years, in Portuguese, English and Spanish. The results showed that such action must be initiated from conception (pregnancy) and perpetuated after birth, in the puerperium. The survival and quality of life of women and children depend on the care provided, and this care must be carried out in a humanized and ethical manner. Thus, we can conclude that care policies should seek to intensify care for the newborn in the first week after delivery, a period in which the highest number of infant deaths is concentrated. Therefore, we seek to provide care for the mother / child in the most diverse strategic ways, including through home visits by the family health teams, an attention recommended by the Ministry of Health to be carried out in the newborn’s first week of life, in addition to all the woman’s pregnancy monitoring.